2012
DOI: 10.2337/dc12-0087
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association Between Serum Level of Glyceraldehyde-Derived Advanced Glycation End Products and Vascular Inflammation Evaluated by [18F]Fluorodeoxyglucose Positron Emission Tomography

Abstract: OBJECTIVEAdvanced glycation end products (AGEs) evoke inflammatory reactions, contributing to the development and progression of atherosclerosis. We investigated the relationship between serum AGE level and vascular inflammation.RESEARCH DESIGN AND METHODSThe study involved 275 outpatients at Kurume University, Japan (189 males and 86 females; mean age 61.2 ± 8.8 years) who underwent complete history and physical examinations and determinations of blood chemistry and anthropometric variables, including AGEs. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 35 publications
1
90
1
Order By: Relevance
“…The characterization of AGEs measured is important to interpret the present data and to make a detailed comparison with previous reports. There are multiple types of immunologically distinct and structurally identified AGEs such as glyoxal and methylglyoxal hydroimidazolones, pyrraline, and pentosidine in humans (35,36). However, they constitute a small percentage of circulating AGEs in vivo, and their biological relevance in endothelial dysfunction has remained unclear (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The characterization of AGEs measured is important to interpret the present data and to make a detailed comparison with previous reports. There are multiple types of immunologically distinct and structurally identified AGEs such as glyoxal and methylglyoxal hydroimidazolones, pyrraline, and pentosidine in humans (35,36). However, they constitute a small percentage of circulating AGEs in vivo, and their biological relevance in endothelial dysfunction has remained unclear (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although glyceraldehyde, which could be derived from glucose metabolism, is not a major sugar in vivo, and its incubation with proteins will generate a large number of structurally unidentified AGEs, and we cannot identify the structure of AGEs measured in this study, our study suggests the clinical utility of measurement of the ratio of serum levels of glyceraldehyde-derived AGEs to sRAGE for detecting endothelial dysfunction in humans. In regard to the characterization of AGEs measured, we previously reported that antibodies raised against glyceraldehyde-derived AGEs used for the ELISA did not crossreact with early glycation products (HbA 1c and/or fructoselysine) or structurally identified AGEs such as glyoxal and methylglyoxal hydroimidazolones, CML, carboxyethyllysine, or pentosidine (35,36). So, these structurally identified AGEs were not evaluated in our ELISA system, although methylglyoxal hydroimidazolone could be formed through both glyceraldehyde-related and methylglyoxal-related pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, we have found that glyceraldehyde-derived AGE levels are (a) correlated with a soluble form of RAGE that could reflect tissue RAGE expression in both nondiabetic and diabetic subjects (104)(105)(106)(107), thus suggesting a marker of the activation of AGE-RAGE axis; (b) associated with low-density lipoprotein cholesterol levels and thrombogenic markers such as plasminogen activator inhibitor-1 and fibrinogen in a general population (108)(109)(110); (c) elevated under oxidative stress, chronic kidney disease and/or diabetic conditions and corre-lated with inflammatory biomarkers such as monocyte chemoattractant protein-1, the soluble form of vascular cell adhesion molecule-1 and ADMA (106,107,(111)(112)(113); (d) increased in nonalcoholic steatohepatitis (NASH) patients and associated with insulin resistance in both NASH subjects and an non-NASH general population (114)(115)(116); (e) correlated with serum PEDF and DPP-4 levels, markers of insulin resistance (117,118); (f) associated with visceral and subcutaneous adipose tissue inflammation and decreased adiponectin levels (114,119); (g) correlated with vascular inflammation and endothelial dysfunction in high-risk patients (120,121); (h) inversely associated with number and migratory activity of EPCs (122), thus suggesting the involvement of this type of AGEs in impaired endothelial cell repair; and (i) significantly associated with plaque progression in patients with acute coronary syndrome (123). Moreover, atrovastatin, pioglitazone and α-glucosidase inhibitor have been shown to significantly decrease serum levels of glyceraldehyde-derived AGEs, which are associated with reduced biomarker levels for organ damage in diabetic, chronic kidney disease or NASH subjects (120,(124)(125)(126)(127)(128).…”
Section: Measuring Serum Levels Of Ages and Its Clinical Utilitymentioning
confidence: 99%